Conditioned Medium of Human Menstrual Blood-Derived Endometrial Stem Cells Protects Against MPP+-Induced Cytotoxicity in vitro - Li, Han; Yahaya, Badrul Hisham; Ng, Wai Hoe; Yusoff, Narazah Mohd; Lin, Juntang (Frontiers in Molecular Neuroscience, 2019)
Mesenchymal stem cells (MSCs) showed the potential to treat Parkinson’s disease (PD). However, it is unknown whether conditioned medium of human menstrual blood-derived endometrial stem cells (MenSCs-CM) has function to alleviate syndromes of PD. In this study, human neuroblastoma SH-SY5Y cells were exposed to neurotoxicant 1-methyl-4-phenylpyridinium (MPP+) for inducing a range of response characteristics of PD. After culturing this cell model with 24h/48h collected MenSCs-CM for different days, cell viability, pro-inflammation cytokines, mitochondrial membrane potential (Δψm), oxidative stress, and cell apoptosis were detected. Finally, protein assay was performed to detect 12 kinds of neurotrophic factors inside MenSCs-CM. Our results showed that MPP+ caused SH-SY5Y cell viability reduction as an increasing dose and time dependent manner. MPP+ treatment resulted in inflammation, mitochondrial dysfunction, reactive oxygen species (ROS) production accumulation, and apoptosis of SH-SY5Y at its IC50 concentration. 48h-collected MenSCs-CM and culturing with the MPP+-treated SH-SY5Y for 2 days are the optimized condition to increase cell viability. Besides, MenSCs-CM was efficacious against MPP+ induced inflammation, Δψm loss, ROS generation, and it could significantly decrease cells numbers in late apoptosis stage. What’s more, protein assay showed that MenSCs-CM contained various neuroprotective factors. Our study provided the first evidence that MenSCs-CM has protective effect on MPP+- induced cytotoxicity in various aspects, and firstly showed that MenSCs can release at least 12 kinds of neurotrophic factors to medium, which may contribute to the protective function of MenSCs-CM to treat PD. This research enlightening that MenSCs-CM is beneficial in the therapy for Parkinson’s disease and probably also for other neurodegenerative diseases.